Fungicides application in corn disease control and mycotoxin accumulation in grain - Seidel, Gilmar; Wesp, Caroline; Koefender, Jana; Pascoal Golle, Diego; Schoffel, André; Deuner, Elaine; Nicolodi Camera, Juliane (International Journal for Innovation Education and Research, 2020)
In Brazil, corn planted area increased by 30%. Therefore, there was also an increase in the incidence of pathogens in the crop. The objective of this work was to evaluate the influence of fungicide applications on corn crops in the different growth stages for the control of the diseases and its effect on the occurrence of mycotoxins in the grain. The experiment was carried out in the 2017/2018 summer crop, in the municipality of Cruz Alta, state of Rio Grande do Sul/BR. This study used P 1630 hybrid, in a randomized block design with eight treatments (control, V8, PT, V4 + V8, V4 + V8 + PT, V8 + PT, V8 + PT + 15, PT + 15) and three replicates. The fungicide fluxapiroxade + pyraclostrobin + epoxiconazole at the dose of 1.0 L/ha-1 was used. The diseases that affected the crop were the white spot and helmintosporiosis, therefore, reducing the incidence of diseases. Also the highest yields were obtained where the applications started at the phenological stage V4 and V8. The levels of mycotoxins detected in this work remained within the limits of the legislation, with a significant reduction in the accumulation of fumonisin and aflatoxin with fungicide applications.